The effect of Nigella sativa and zinc on IgE and IL-5 serum levels, the experimental study in ovalbumin induced BALB/C mice - Rahmawati, Fany D.; ., Suprihati; Santosa, Yanuar I.; Yusmawan, Willy; Dewi, Anna M. K.; Budiarti, Rery; Yunika, Kanti (International Journal of Research in Medical Sciences, 2021)
Background: Allergy is a hypersensitivity reaction due to induction of specific IgE binding to allergens on the surface of mast cells. Interleukin-5 is an important marker of hypersensitivity inflammation reactions. Nigella sativa, contain active substance thymoquinone, can reduce inflammatory mediators. Zinc as anti-inflammatory by inhibit releasing mediators from mast cells. Objective was to determine the effect of Nigella sativa (NS) and zinc on IgE and IL-5 serum levels on ovalbumin-induced BALB/C mice. Methods: The study design was a true experiment with post-test only control group using BALB/C mice. The study was conducted at Sultan Agung Islamic University’s laboratory on March-June 2020. Inclusion criteria were female BALB C mice, 6-8 weeks, 22-25 grams, and healthy. Thirty mice were divided randomly into 5 groups; negative control, positive control, NS group, zinc group, and NS + zinc group. All groups treated for 28 days. Allergic reactions tested by skin test with OVA, intervention response assessed by IgE and IL-5 serum levels. Results: At the end of study completed, obtained 6 negative controls, 6 positive controls, 6 NS groups, 5 zinc groups, and 5 NS+zinc groups. Two mice s died before intervention completed. Serum IgE and IL5 levels were significantly difference between treatment groups (Kruskal Wallis test; p=0.007 and One-way ANOVA test; p=0.020). The result of logistic regression test, IgE levels was the most significant in the NS+zinc group (p=0.006) and IL-5 levels was the most significant in the zinc group (p=0.002) Conclusions: Nigella sativa, zinc, and its combination can reduce IgE and IL-5 serum levels of ovalbumin-induced BALB / C mice.